2013
DOI: 10.1016/j.addbeh.2012.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cessation: Understanding barriers and motivations to quitting among urban adult daily tobacco smokers

Abstract: Introduction Many people continue to smoke tobacco products despite known negative health consequences, including increased risk of chronic disease and death. Disparities exist in rates of smoking and chronic disease, underscoring the importance of understanding the barriers and motivations to smoking cessation among vulnerable populations, such as socioeconomically disadvantaged people of color. Methods This study uses data from a cross-sectional randomized household survey conducted in six low-income neigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 14 publications
2
52
0
Order By: Relevance
“…These results are consistent with results of another study that also indicated the expenses arising from purchase of cigarettes as motivational themes to quit smoking, as well as the harmful effects on health resulting from the addiction (23) . On the other hand, taking into account the income of smokers, the price of cigarettes must be substantial to affect the motivation to quit the habit (11) .…”
Section: Discussionsupporting
confidence: 82%
“…These results are consistent with results of another study that also indicated the expenses arising from purchase of cigarettes as motivational themes to quit smoking, as well as the harmful effects on health resulting from the addiction (23) . On the other hand, taking into account the income of smokers, the price of cigarettes must be substantial to affect the motivation to quit the habit (11) .…”
Section: Discussionsupporting
confidence: 82%
“…The smoker's social network has been cited as an important barrier/motivator in other studies [26,29,33], and several caregivers in this study also cited their social network as a barrier. Some caregivers indicated that smoking was common in their social circle, which made it challenging to reduce SHSe; this aligns with previous research that AfricanAmerican smokers perceive smoking as normative among other African-Americans [35].…”
Section: Discussionmentioning
confidence: 71%
“…For example, a study of barriers to HSBs for rural White and African-American adults found similar emphasis on social network and other smokers inside the home [29]. Social network and finances have also been previously cited as both barriers and motivators for cessation among urban smokers in New Haven, Connecticut [33], and concerns regarding the physical appearance of homes have been cited as a potential motivator for HSBs in disadvantaged caregivers in the United Kingdom [28]. Health has also been highlighted; in a study of barriers to cessation in mostly White adult smokers in Tennessee, the most commonly identified motivator of cessation was the improvement of the smoker's general health [34].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of women who quit smoking gain 8 to 10 lb on average [9][10][11][12][13]. Many women smokers report concerns about weight gain as a barrier to quitting [14][15][16][17][18][19][20][21][22][23][24][25], and women quitters who return to smoking identify weight gain as a reason for their relapse [26][27][28][29]. Women who are highly concerned about their weight are more likely to smoke as a means to control their weight [15,30,31].…”
Section: Introductionmentioning
confidence: 99%